Changes of Cadmium Storage Forms and Isotope Ratios in Rice During Grain Filling - Wiggenhauser, Matthias; Aucour, Anne-Marie; Telouk, Philippe; Blommaert, Hester; Sarret, Géraldine (Frontiers in Plant Science, 2021)
Rice poses a major source of the toxic contaminant cadmium (Cd) for humans. Here, we elucidated the role of Cd storage forms (i.e. the chemical Cd speciation) on the dynamics of Cd within rice. In a pot trial, we grew rice on a Cd contaminated soil in upland conditions and sampled roots and shoots parts at flowering and maturity. Cd concentrations, isotope ratios, Cd speciation (X-ray absorption spectroscopy), and micronutrient concentrations were analyzed. During grain filling, Cd and preferentially light Cd isotopes were strongly retained in roots where the Cd storage form did not change (Cd bound to thiols, Cd-S = 100%). In the same period, no net-change of Cd mass occurred in roots and shoots and the shoots became enriched in heavy isotopes (Δ114/110Cdmaturity-flowering = 0.14 ± 0.04 ‰). These results are consistent with a sequestration of Cd in root vacuoles that includes strong binding of Cd to thiol containing ligands that favor light isotopes, with a small fraction of Cd strongly enriched in heavy isotopes being transferred to shoots during grain filling. The Cd speciation in the shoots changed from predominantly Cd-S (72%) to Cd bound to O ligands (Cd-O, 80%) during grain filling. Cd-O may represent Cd binding to organic acids in vacuoles and/or binding to cell walls in the apoplast. Despite this change of ligands, which was attributed to plant senescence, Cd was largely immobile in the shoots since only 0.77% of Cd in the shoots were transferred into the grains. Thus, both storage forms (Cd-S and Cd-O) contributed to the retention of Cd in the straw.. Cd was mainly bound to S in nodes I and grains (Cd-S > 84%) and these organs were strongly enriched in heavy isotopes compared to straw (Δ114/110Cdgrains/nodes-straw = 0.66 to 0.72 ‰) and flag leaves (Δ114/110Cdgrains/nodes-flag.leaves = 0.49 to 0.52 ‰). Hence, xylem to phloem transfer in the node favors heavy isotopes and the Cd-S form may persist during the transfer of Cd from node to grain. This study highlights the importance of Cd storage forms during its journey to grain and potentially into the food chain.